'Black holes in the fabric of the nation': refugees in Mohsin Hamid's Exit West. Issue 2 (3rd April 2019) - Perfect, Michael
ABSTRACT: This article explores the representation of refugees in Mohsin Hamid's Exit West, a novel which has been widely celebrated for its response to the refugee crisis of its contemporary moment. In a distinct echo of Salman Rushdie's claim, thirty-five years earlier, that it 'may be argued that the past is a country from which we have all emigrated', Hamid's novel similarly claims that 'we are all migrants through time.' Moreover, like Rushdie's fiction, Hamid's novel incorporates elements of magical realism: its protagonists escape their unnamed war-torn city through a 'door' that instantaneously transports them to Mykonos, and they subsequently travel through other such 'doors' to London and California. Their story is interspersed with a series of vignettes in which other migrants also find themselves magically transported across national borders. As well as considering the ways in which Hamid's novel seeks to humanise refugees, this article considers the novel's evocation of a world in which human beings – like capital, images, and (mis)information – have gained access to largely ungovernable networks of instantaneous travel across vast distances. It argues that Hamid's novel is not just 'about' refugees but also constitutes a reflection on how they and their journeys are represented and mediated by actually-existing technologies.